Acute liver injury following turmeric use in Tuscany: An analysis of the Italian Phytovigilance database and systematic review of case reports. Issue 3 (20th July 2020) - Lombardi, Niccolò; Crescioli, Giada; Maggini, Valentina; Ippoliti, Ilaria; Menniti‐Ippolito, Francesca; Gallo, Eugenia; Brilli, Valentina; Lanzi, Cecilia; Mannaioni, Guido; Firenzuoli, Fabio; Vannacci, Alfredo
Abstract : Aims: Several cases of acute non‐infectious cholestatic hepatitis recently appeared in Italy following consumption of Curcuma longa ‐containing dietary supplements. The aim of this research was to describe the Tuscan (Italy) cases of acute hepatitis and to compare them with similar cases of hepatotoxicity published in the literature by performing a systematic review. Methods: Records of Tuscan cases of acute hepatitis were obtained from the Italian Phytovigilance system. Each spontaneous report was analysed in order to collect all relevant clinical information of patients and information concerning the Curcuma longa ‐containing dietary supplement. Moreover, both the RUCAM and WHO‐UMC systems were used to evaluate the causal relationship between the use of dietary supplement and acute hepatitis. A systematic literature review was performed in MEDLINE and Embase and all case‐reports and case‐series published in English were included. Results: Seven cases of acute hepatitis occurring in Tuscany up to September 2019 are described. In all cases, hepatotoxicity was associated with Curcuma longa formulations with high bioavailability and high dosage of curcumin/curcuminoids. The causal relationship was also supported by the positive dechallenge observed in most cases. In the 23 cases identified through the systematic review, the majority of patients were concomitantly exposed to at least one other medication and 16 of them experienced a positive dechallenge. Conclusions: Within the frame of poorly controlled and regulated products, such as dietary supplements, the evaluation of Italian cases of Curcuma longa ‐induced acute hepatitis and the systematic review of literature confirmed the association between Curcuma longa and liver injury.